ANALISIS PENDISTRIBUSIAN DAGING QURBAN BAGI MASYARAKAT MUSLIM DAN NON MUSLIM DITINJAU DARI FIKIH (Studi kasus di Yayasan Darussalam Desa Sambiroto Kecamatan Baron Kabupaten Nganjuk) - Alwi Musa Muzaiyin (Fakultas Syariah IAIN Kediri, 2023)
Economic activities in human life certainly cannot be separated from activities called distribution. Distribution itself is an activity of distributing goods or services. Whereas in Islam, distribution itself is the activity of distributing wealth so that the circulation of wealth is evenly distributed so that it does not only circulate within certain groups. One of the facts that is contradictory in society is the distribution of qurbani meat which is also intended for non-Muslims, where the system of justice and solidarity is the reason for this distribution. Not only that, contradictions also arise when the distribution of qurbani meat is given to people who are classified as rich or capable. This paper tries to answer the contradiction that arises. For this reason, in this article, researchers used library research methods and field research using interview tests. The type of data used is data obtained directly from the research object.